Choosing justice : an experimental approach to ethical theory - Frohlich, Norman (California series on social choice and political economy ;, 1992)
This book presents an entirely new answer to the question: "What is fair?" In their radical approach to ethics, Frohlich and Oppenheimer argue that much of the empirical methodology of the natural sciences should be applied to the ethical questions of fairness and justice.